L’instrumentalisation de l’espace - Gatien Elie; Elisabeth Foscolo (EchoGéo)
Encampement localization partly explains the media success of the homeless people movement Les Enfants de Don Quichotte during winter 2006-2007. In Paris and in the rest of France, tents were located in touristic areas or in symbolic places to gain visibility. The invisibles claimed their right to city againt urbanism policies wich drive the poor outside downtown since the XIXth century. Those encampements had a double effect. They put the accomodation problem on politics diary and they reminded the middle class people of their precarity by the sudden nearness of the otherness.